Metrics for rate maximization in multiuser-MISO systems with Zero-Forcing Beamforming - Castañeda, Eduardo
In this work we present a unified treatment on the most common metrics used in the utility function of state-of-the-art user selection algorithms for sum rate maximization in MISO systems under Zero-Forcing Beamforming. We present the way that such metrics are used to maximize the total sum rate and the relations held among each other. Via simulation we found upper bounds of the average total sum rate for each metric which allow us to establish a benchmark in terms of sum rate performance and a trade-off between the metric accuracy needed to maximize the sum rate and the computational complexity required to determine each metric.